Exploring the relationship between trout fishing and wellbeing: insights from Aotearoa New Zealand trout anglers - Cohen Stewart; Iritana Bennett-Fakahau; Shyamala Nada-Raja; Kayla Stewart (Kōtuitui)
Internationally, there is growing interest in understanding the potential for recreational fishing to enhance the wellbeing of participants. To date, no studies have investigated the potential for recreational trout fishing to influence wellbeing in the Aotearoa New Zealand context. To address this gap, nine semi-structured interviews were conducted with anglers in the local community and explored their understanding of wellbeing and how they percieve trout fishing contributes to their wellbeing. The interviews were audio-recorded, transcribed, analysed thematically, and examined using the Te Whare Tapa Whā model of holistic wellbeing. For trout anglers, wellbeing incorporated mental, physical, spiritual, and relational health. Trout fishing was perceived as enhancing these elements of wellbeing by fostering positive states of being; cultivating connection with self, others, place and nature; allowing for disconnection from stressors; and providing physical exercise. These exploratory findings highlight the potential for trout fishing to enhance all dimensions of holistic wellbeing within the Te Whare Tapa Whā model and a need for further research in this area.